2007
DOI: 10.1139/y07-105
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic properties of polysaccharide- and polyphenolic-enriched fractions from the brown seaweedAscophyllum nodosumThis article is one of a selection of papers published in this special issue (part 2 of 2) on the Safety and Efficacy of Natural Health Products.

Abstract: Abstract:We screened seaweed species from Atlantic Canada for antidiabetic activity by testing extracts for a-glucosidase inhibitory effect and glucose uptake stimulatory activity. An aqueous ethanolic extract of Ascophyllum nodosum was found to be active in both assays, inhibiting rat intestinal a-glucosidase (IC 50 =7 7mg/mL) and stimulating basal glucose uptake into 3T3-L1 adipocytes during a 20-minute incubation by about 3-fold (at 400 mg/mL extract). Bioassay-guided fractionation of the A. nodosum extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 28 publications
(23 reference statements)
2
33
0
2
Order By: Relevance
“…The ability of a phytocomplex obtained from these algae to inhibit both enzymes has already been demonstrated by Roy et al [32], and was confirmed in this research. In particular, the IC 50 value of this extract for α-amylase inhibition was 10 to 1000-fold lower than that reported for algae extracts prepared with solvents [17], fruit extracts [38], or polyphenols obtained from other plants [39,40]. Moreover, the Ki value (6.0 × 10 −8 M) indicated a strong affinity of binding the algae inhibitory component to α-amylase.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The ability of a phytocomplex obtained from these algae to inhibit both enzymes has already been demonstrated by Roy et al [32], and was confirmed in this research. In particular, the IC 50 value of this extract for α-amylase inhibition was 10 to 1000-fold lower than that reported for algae extracts prepared with solvents [17], fruit extracts [38], or polyphenols obtained from other plants [39,40]. Moreover, the Ki value (6.0 × 10 −8 M) indicated a strong affinity of binding the algae inhibitory component to α-amylase.…”
Section: Discussionmentioning
confidence: 55%
“…Algae extracts are considered a good source of digestive enzyme inhibitors. In particular, they contain polyphenolic compounds, such as bromophenols [15,16] and phlorotannins (PHTs) [5,17], which are well known α-glucosidase inhibitors. The enzyme α-glucosidase, together with α-amylase, is a key enzyme in starch breakdown and absorption.…”
Section: Introductionmentioning
confidence: 99%
“…and particularly from A. nodosum have demonstrated promising effects against these enzymes (Table 2). Per Zhang et al [45], the inhibitory effects of different fractions from A. nodosum ethanol 50% extracts towards α-glucosidase activity was highly correlated with their phlorotannin content, as the lowest IC 50 value (24.0 μg/mL) was observed for the C18 purified ethyl acetate fraction (TPC = 70.2% PE), followed by non-purified ethyl acetate fraction (IC 50 = 38.0 μg/mL; TPC = 39.8% PE) and crude ethanol extract (IC 50 = 77.0 μg/mL; TPC = 22.5% PE). When comparing the α-glucosidase inhibitory activities of ethanol 96% and acetone 70% extracts from A. nodosum and F. vesiculosus , both rich in phlorotannins, to that of acarbose (i.e., a well-known inhibitor of α-glucosidase and α-amylase currently used as an antidiabetic drug), IC 50 values of 8.9 and 0.72 μg/mL, respectively, for the former, and 4.4 and 0.34 μg/mL, respectively, for the latter were obtained, corresponding to an inhibitory activity 160–2000-times stronger than that of acarbose (IC 50 = 720 μg/mL) [111].…”
Section: Biological Activitiesmentioning
confidence: 99%
“…F. vesiculosus has also been commonly used for the treatment of rheumatoid arthritis, asthma, atherosclerosis, psoriasis and skin diseases, as well as several other complications [35,36,37]. Likewise, Ascophyllum and Pelvetia are endowed with several medicinal properties including antioxidant [38,39], anticoagulant [40,41], anti-inflammatory [41,42], antitumor [43,44] and antidiabetic [45,46,47], among others. In addition, these Fucaceae can be currently found in the ingredient labels of a dozen cosmetic products used as antiaging, anti-wrinkle, anti-photoaging, slimming, moisturizing and skin-whitening agents [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive components in seaweeds include polyphenols, peptides, and polysaccharides (Zhang et al, 2007; Jimenez-Escrig et al, 2011). Many of these active compounds were useful functional ingredients with numerous health benefits (Yuan and Walsh, 2006; Kim and Joo, 2008).…”
Section: Introductionmentioning
confidence: 99%